Pengaruh Model Pembelajaran Peer Led Guided Inquiry (PLGI) terhadap Kompetensi Literasi SainsSiswa ditinjau dari Kemampuan Akademik - Sri Lestari; Meti Indrowati; Dewi Puspita Sari (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
The purposes of this research are to ascertain: 1) the influence of Peer Led Guided Inquiry model towards competency of scientific literacy, 2) the influence of academic ability toward competency of scientific literacy. The research was quasi experiment research. The research was designed using posttest-only group design with factorial design 2 x 3. The population of this research were all of 11th degree student at SMA N 2 Sukoharjo in academic year 2018/2019. The sample of this research were student of XI MIPA 3 as experiment group and XI MIPA 4 as control group. The sample of this research was established by cluster random sampling. The data was collected essay test, observation form, and document. The hypotheses analyzed by Anova Two Ways. The research concluded that 1) Peer Led Guided Inquiry (PLGI) model had significant effect toward competency of scientific literacy, 2) the academic ability didn’t has significant effect toward competency of scientific literacy.